Comparative Genomic Analysis of Campylobacter Plasmids Identified in Food Isolates - Yiping He; Gretchen Elizabeth Dykes; Siddhartha Kanrar; Yanhong Liu; Nereus W. Gunther; Katrina L. Counihan; Joe Lee; Joseph A. Capobianco (Microorganisms)
Campylobacter is one of the leading bacterial causes of gastroenteritis worldwide. It frequently contaminates poultry and other raw meat products, which are the primary sources of Campylobacter infections in humans. Plasmids, known as important mobile genetic elements, often carry genes for antibiotic resistance, virulence, and self-mobilization. They serve as the main vectors for transferring genetic material and spreading resistance and virulence among bacteria. In this study, we identified 34 new plasmids from 43 C. jejuni and C. coli strains isolated from retail meat using long-read and short-read genome sequencing. Pangenomic analysis of the plasmid assemblies and reference plasmids from GenBank revealed five distinct groups, namely, pTet, pVir, mega plasmids (>80 kb), mid plasmids (~30 kb), and small plasmids (<6 kb). Pangenomic analysis identified the core and accessory genes in each group, indicating a high degree of genetic similarity within groups and substantial diversity between the groups. The pTet plasmids were linked to tetracycline resistance phenotypes in host strains. The mega plasmids carry multiple genes (e.g., aph(3’)-III, type IV and VI secretion systems, and type II toxin–antitoxin systems) important for plasmid mobilization, virulence, antibiotic resistance, and the persistence of Campylobacter. Together, the identification and comprehensive genetic characterization of new plasmids from Campylobacter food isolates contributes to understanding the mechanisms of gene transfer, particularly the spread of genetic determinants of virulence and antibiotic resistance in this important pathogen.